Extending the UTAUT Model to Examine the Influence of Social Media on Tourists’ Destination Selection - Sharma, Nidhi; Khatri, Bhanupriya; Khan, Shad Ahmad; Shamsi, Mohd Salman (Indian Journal of Marketing, 2023)
Purpose : The main goal of this study was to examine social media’s influence on tourists while selecting a destination. Methodology : The data were gathered using a purposive sampling technique from 340 visitors of tourist destinations in tri-city (Chandigarh, Mohali, and Panchkula) and Delhi. The sampled group consisted of travelers who accessed social media platforms. PLS-SEM 3.3.3 version was used for data analysis. Findings : When it comes to the selection of destinations, social media has a significant influence on visitors’ decision-making. The results of this study revealed that performance expectancy, social influence, perceived risk, effort expectancy, and perceived trust significantly influenced behavioral intentions to use social media for destination selection. The determinants, such as habit and behavioral intentions, influenced tourists’ actual usage of social media. Implications : The study’s findings are meant to provide the major participants in the tourism industry with insights into tourists’ behavior. All the parties involved in the tourism business must understand the pertinence of social media. To reach customers who prefer to use technology-based solutions, social media networking sites are essential. Also, including social media in a marketing strategy makes it possible to provide users with adequate and necessary information. Originality : This research concentrates on web-based technology, such as social media, to better understand how it influences visitors when they use these technologies to choose their destinations by posing questions to scholars and practitioners.